The impact of organic amendments on forest soil properties under Mediterranean climatic conditions - Hueso-González, Paloma; Martínez-Murillo, Juan Francisco; Ruiz-Sinoga, José Damián (Wyley, 2014)
Restoring the native vegetation is one of the most effective ways to control soil degradation in Mediterranean areas, especially in verydegraded areas. In the initial months after afforestation, vegetation cover establishment and soil quality could be better sustained if the soilwas amended with an external extra source of organic matter. The goal of this study was to test the effect of various organic amendments onselect soil properties [soil organic carbon (SOC), pH, and electrical conductivity (EC)] over a 24-month period. Four amendments wereapplied in an experimental set of plots: straw mulching (SM), mulch with chipped branches of Aleppo Pine (Pinus halepensisL.; PM), sheepmanure compost (SH), and sewage sludge (RU). Plots were afforested following the same spatial pattern, and amendments were mixed withthe soil at the rate 10 Mg ha 1. Organic amendments helped maintain SOC over the initial 6 months after the afforestation. However, only theSM and PM treatments had increased SOC values after 24 months. Decreases in EC were found after the addition of SM, PM, and SHamendments. However, RU increased EC values 24 months after the afforestation. Variations in pH values were not sufficient to establishdifferences among the various treatments. Furthermore, the results show that forest soils with or without organic amendments respondedsimilarly to the seasonal changes in Mediterranean conditions.
Copyright © 2014 John Wiley & Sons, Ltd Política de acceso abierto tomada de: https://v2.sherpa.ac.uk/id/publication/3525?template=romeo
Keywords: Suelos - Permeabilidad; Suelos - Geografía; Mediterráneo (Región) - Clima; Soil organic carbon; PH; Electrical conductivity; Soil organic amendment; Mediterranean climatic seasonality